2010
DOI: 10.1016/j.schres.2010.02.913
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction in Unaffected First-Degree Relatives of Patients Suffering From Schizophrenia

Abstract: Recent studies revealed cardiac autonomic dysfunction in patients with acute schizophrenia, which appears to be mainly related to reduced vagal and increased sympathetic modulation. To understand the significance of cardiac autonomic function in patients with schizophrenia, we extended these studies to relatives of patients. In this study, we assessed cardiac autonomic modulation in healthy first-degree relatives of patients with schizophrenia (n 5 36) to investigate a putative genetic influence. Data were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Since those word types represent in an abstract manner a behavior oppositional to the typical baroreflex response. This finding might be partly interpreted as a loss of baroreflex mediated regulation in relatives and schizophrenic patients and is in accordance with recent results [2,18]. Although, the baroreflex results were assessed by the well establish sequence method a posture change and pharmacological manipulation might further confirm this result.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Since those word types represent in an abstract manner a behavior oppositional to the typical baroreflex response. This finding might be partly interpreted as a loss of baroreflex mediated regulation in relatives and schizophrenic patients and is in accordance with recent results [2,18]. Although, the baroreflex results were assessed by the well establish sequence method a posture change and pharmacological manipulation might further confirm this result.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest an autonomic dysregulation and a possible genetic background in patients and their In accordance with our hypotheses we found comparable patterns of altered autonomic function in healthy first-degree relatives and in patients suffering from schizophrenia [2][3][4]. The alterations of cardiovascular variabilities might reflect an autonomic dysregulation by a partly increased sympathetic and reduced parasympathetic tone in healthy first-degree relatives of patients with schizophrenia [2,18]. Indices based on symbolic dynamics revealed a reduced high variability (phvar10) in relatives and patients indicating predominant sympathetic activation and vagal withdrawal [15].…”
Section: Discussionsupporting
confidence: 89%
“…Berger and his team were among the first to examine QT interval variability of the surface electrocardiogram (ECG) as a means for quantifying temporal repolarization lability [24]. Just as HRV arises primarily from autonomic influence on the sinus node [11], it is tempting to think QT interval variability reflects autonomic modulation of ventricular electrical activity. There are several studies that hypothesize that QT variability is a measure of cardiac sympathetic tone: HRV reflects vagal modulation when vagal activity is high, and mirrors fluctuations in sympathetic activity when the latter is high.…”
Section: Discussionmentioning
confidence: 99%
“…Several research papers indicate that autonomic nervous system (ANS) dysfunction might play an important role in schizophrenia [9,10,11,12]. Patients with schizophrenia have been reported to experience sudden cardiac death 3 times more likely than individuals from the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Other measures of autonomic balance (e.g., pupil function, baroreceptor sensitivity and heart rate variability) have not been investigated as prognostic factors of schizophrenia outcome. A recent study of relatives of patients with schizophrenia found that autonomic cardiac dysfunction was also evident in the relatives, although with attenuated strength [3]. This can be contrasted by another recent study that observed normal cardiac autonomic response to mental stress in relatives to patients with schizophrenia, but an abnormal prolongation of the stress response pattern after termination of the stress stimulus [12].…”
Section: Discussionmentioning
confidence: 99%